Tinjauan Yuridis Praktik Persaingan Tidak Sehat ( Predatory Pricing) Terhadap Kasus Pt. Conch South Kalimantan Cement (Conch) - Yasmin Surya Rahmalia (Jurnal Ilmiah Wahana Pendidikan, 2023)
The practice of selling at a loss or predatory pricing that violates Article 20 of Law No. 5 of 1999 concerning unfair business competition and monopoly is the focus of discussion in this study. The research discusses legal regulations related to sale and loss agreements which can lead to unfair business competition, and analyzes Decision No.3/KPPU-L/2020 which is related to the case of selling at a loss by PT Conch South Kalimantan Cement. The results of the analysis show that the practice of sale and loss agreements is regulated in business competition law regulations, and business actors who carry out these practices violate the provisions of Article 20 Law No.5 of 1999. KPPU's decision Number 03/KPPU-L/2020 is based on an economic approach and law, and PT. Conch South Kalimantan Cement was rejected, strengthening the decisions of the KPPU and the Commercial Court.